Field guide to the birds of Colombia - McMullan, Miles (ProAves, 2010)
With almost 1900 species, Colombia is the world's most bird-rich nation. Never before have so many species been described and ilustrated for a national field guide. Plates are arranged to show ilustrations, maps, text, fieldnotes and notes on endemism and threat status side by side. Emphasis is placed on features that will be most useful in the field.